2017
DOI: 10.30998/scope.v1i01.862
|View full text |Cite
|
Sign up to set email alerts
|

Translation Techniques and Translation Competence in Translating Informative Text for Indonesian EFL Learners

Abstract: Translation skill is viewed as the fifth skill after the other four skills that should be mastered by the second or foreign learner on studying English. This study aims at analyzing and describing translation techniques and translation competence of Indonesian EFL learners. The research was carried by descriptive research method. The number of respondent is 35 students on majoring of English Education, and the translation test as the instrument. The result of descriptive analysis shows that the literal transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
1
12
0
2
Order By: Relevance
“…The translation reflects the knowledge and practical intelligence of the students in learning English (Newmark, 1988) (as cited in Sundari & Febriyanti, 2016) and their ability to deal with the four primary skills in language learning (Malmkjᴂr, 1997) (as cited in Laviosa, 2014). In line with the theories above, it can be concluded that the students' good and excellent ability to translate texts from English into Indonesian reflects their success in comprehending texts in their learning process.…”
Section: Discussion Efl Learners' Translation Abilitymentioning
confidence: 82%
See 1 more Smart Citation
“…The translation reflects the knowledge and practical intelligence of the students in learning English (Newmark, 1988) (as cited in Sundari & Febriyanti, 2016) and their ability to deal with the four primary skills in language learning (Malmkjᴂr, 1997) (as cited in Laviosa, 2014). In line with the theories above, it can be concluded that the students' good and excellent ability to translate texts from English into Indonesian reflects their success in comprehending texts in their learning process.…”
Section: Discussion Efl Learners' Translation Abilitymentioning
confidence: 82%
“…Four skills (listening, speaking, reading, and writing) must be developed and mastered well for EFL learners to communicate and be considered qualified (Derakhshan, 2015). In addition, Newmark (1988) states that translation takes the role of the fifth skill in the final stage of the EFL learning process and is the practical intelligence on developing the language learner competence since it can reflect the knowledge of the target language (as cited in Sundari & Febriyanti, 2016). Malmkjᴂr (1997) argues that translation cannot be separated from the four skills because it involves a good deal of reading, writing, speaking, and listening in a foreign language (as cited in Laviosa, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pergeseran kelas pada contoh 1 merupakan salah satu teknik penerjemahan. Molina dan Albir (2002) dikutip dari (Sundari & Febriyanti, 2016) penerjemahan merupakan prosedur untuk menganalisis dan mengklasifikasikan bagaimana kesepadanan antara bahasa sumber dan sasaran tercapai untuk mempertahankan keakurasian makna. Lebih lanjut, Molina dan Albir (2002) dalam (Dhyaningrum, Nababan, dan Djatmika, 2016) menyebutkan lima karakteristik teknik penerjemahan, yaitu 1) memengaruhi hasil terjemahan, 2) diklasifikasikan dengan perbandingan pada teks BSu, 3) berada pada tataran mikro, 4) tidak saling berkaitan tetapi berdasarkan konteks tertentu, dan 5) bersifat fungsional.…”
Section: Pendahuluanunclassified
“…From the views above, it can be said that translation can be defined as a process as well as a product of translation activity in which render source text into equivalent target text. (Sundari, 2016) Translation plays an important role in bridging the gaps between the different cultures and nations. Literary translations in particular help these different nations reach a universal culture on a common ground.…”
Section: Introductionmentioning
confidence: 99%